Differential expression of cytokines and vitamin D in benign and malignant thyroid diseases - Huimin Li; Xin Jin; Meng Zhang; Xin Wang; Hai Wang (Scientific Reports)
Abstract Given the critical role of cytokines in tumor microenvironment modulation1 and the anti-inflammatory and anti-tumor effects of vitamin D2,3, this study aimed to assess serum levels of IL-4, IL-6, IL-10, IL-17, TNF-α, IFN-γ, and vitamin D in patients with benign thyroid nodules, PTC, and healthy controls, to further elucidate their involvement in thyroid disease progression. Methods: Peripheral blood samples were collected from benign nodule patients (n = 24, pre- and post-operative), PTC (n = 39, pre- and post-operative), and healthy controls (n = 35) who were treated at Tongde Hospital of Zhejiang Province between June 2023 and May 2024. Serum levels of IL-4, IL-6, IL-10, IL-17, TNF-α, and IFN-γ were measured by flow cytometry, while vitamin D levels were determined by chemiluminescent immunoassay. Results: Compared to the healthy control, benign nodule patients showed elevated serum levels of IL-4 (276%), IL-6 (62%), and TNF-α (14%), whereas PTC patients exhibited more pronounced increases in IL-4 (519%), IL-6 (260%), IL-10 (15%), IL-17 (1248%), TNF-α (238%), and IFN-γ (244%), along with significantly decreased vitamin D levels (47.4%).When compared with benign nodule patients, PTC patients demonstrated significantly higher levels of IL-4 (65%), IL-6 (122%), IL-10 (14%), IL-17 (395%), TNF-α (195%), and IFN-γ (62%), as well as lower vitamin D levels (44.0%). Postoperatively, serum IL-4 (66.9%) and IL-6 (13.1%) levels decreased in benign nodule patients, while PTC patients showed reductions in IL-4 (75.4%), IL-6 (34.7%), IL-10 (16.5%), IL-17 (81.5%), and TNF-α (82.0%) levels, with unchanged vitamin D levels in both groups. Notably, positive correlations were observed between IL-4/IL-17(r = 0.545, P = 0.006) in benign nodule patients and IL-4/TNF-α (r = 0.316, P = 0.049), IL-10/IFN-γ (r = 0.458, P = 0.003) in PTC patients, whereas an inverse correlation was found between vitamin D and IL-17 in PTC patients (r=-0.444, P = 0.005). ROC analysis revealed that serum IL-17(AUC = 0.895, P < 0.001) and vitamin D (AUC = 0.982, P < 0.001) had good discriminative power between benign nodule patients and PTC patients. Multivariate analysis confirmed that vitamin D served as an independent protective predictor for malignant thyroid nodules (OR = 0.542, P = 0.008), while IL-17 showed a trend toward being a risk factor (OR = 1.415), though the statistical significance was marginal (P = 0.082). Conclusion: This study confirms that both benign and malignant thyroid diseases exhibit upregulated cytokine expression (more pronounced in PTC patients), which decreases postoperatively, supporting the inflammatory role in thyroid disease progression. The study found significant differences in the expression of IL-17 and vitamin D in benign and malignant thyroid diseases, with abnormally elevated IL-17 and vitamin D deficiency observed in PTC patients, along with a significant negative correlation between the two. Multivariate analysis confirmed vitamin D as an independent protective factor against malignant thyroid nodules (OR = 0.542, P = 0.008), while IL-17 showed a trend toward being a risk factor (OR = 1.415), though statistical significance was marginal, possibly due to limited sample size. This finding holds important clinical implications: preoperative combined detection of serum IL-17 and vitamin D levels may help predict the malignancy risk of nodular thyroid disease, improving diagnostic accuracy and reducing unnecessary thyroidectomies caused by indeterminate fine-needle aspiration cytology results. Further validation in larger cohorts is warranted to establish their clinical utility. This study provides critical guidance for developing novel biomarker panels for thyroid cancer diagnosis.